2021
DOI: 10.1155/2021/9483892
|View full text |Cite
|
Sign up to set email alerts
|

On the Connected Safe Number of Some Classes of Graphs

Abstract: For a connected simple graph G , a nonempty subset S of V G is a connected safe set if the induced subgraph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The authors in [12] explored the connection between the SN and integrity in a connected graph. Iqbal et al in [16] presented the CSS of ladder, wheel, and sunlet graphs, even though there is no known algorithm to find the minimum SS and CSS of any connected graph. Furthermore, some authors in [17] studied the SS and computed the SN and CSN of a cartesian product of two complete graphs.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [12] explored the connection between the SN and integrity in a connected graph. Iqbal et al in [16] presented the CSS of ladder, wheel, and sunlet graphs, even though there is no known algorithm to find the minimum SS and CSS of any connected graph. Furthermore, some authors in [17] studied the SS and computed the SN and CSN of a cartesian product of two complete graphs.…”
Section: Introductionmentioning
confidence: 99%
“…al. [13] presented the CSS of the ladder, wheel, and sunlet graphs. In addition, some authors studied CSS and computed CSN of different classes of graphs which are shown in Table 1 :…”
Section: Introductionmentioning
confidence: 99%